Spinoza : a very short introduction - Scruton, Roger (New York : Oxford University Press, 2002)
A concise overview of the life and thought of seventeenth-century Dutch philosopher Benedict de Spinoza.
Includes bibliographical references (p. 119-121) and index.
Adult
Keywords: Spinoza, Benedictus de, -- 1632-1677.; Spinoza, Benedictus de, -- 1632-1677.; Philosophy, Dutch; Dutch philosophy